A Benchmark Study of Burning Rate of Selected Thermites through an Original Gasless Theoretical Model - Sarah Brotman; Mehdi Djafari Rouhani; Samuel Charlot; Alain Estève; Carole Rossi (Applied Sciences, 2021)
This paper describes a kinetic model dedicated to thermite nanopowder combustion, in which core equations are based on condensed phase mechanisms only. We explore all combinations of fuels/oxidizers, namely Al, Zr, B/CuO, Fe2O3, WO3, and Pb3O4, with 60 % of the theoretical maximum density packing, at which condensed phase mechanisms govern the reaction. Aluminothermites offer the best performances, with initiation delays in the range of a few tens of microseconds, and faster burn rates (60 cm s−1 for CuO). B and Zr based thermites are primarily limited by diffusion characteristics in their oxides that are more stringent than the common Al2O3 barrier layer. Combination of a poor thermal conductivity and efficient oxygen diffusion towards the fuel allows rapid initiation, while thermal conductivity is essential to increase the burn rate, as evidenced from iron oxide giving the fastest burn rates of all B- and Zr-based thermites (16 and 32 cm·s−1, respectively) despite poor mass transport properties in the condensed phase; almost at the level of Al/CuO (41 versus 61 cm·s−1). Finally, formulations of the effective thermal conduction coefficient are provided, from pure bulk, to nanoparticular structured material, giving light to the effects of the microstructure and its size distribution on thermite performances.